1974
DOI: 10.1172/jci107688
|View full text |Cite
|
Sign up to set email alerts
|

A Biochemical Abnormality in Cerebrotendinous Xanthomatosis IMPAIRMENT OF BILE ACID BIOSYNTHESIS ASSOCIATED WITH INCOMPLETE DEGRADATION OF THE CHOLESTEROL SIDE CHAIN

Abstract: A B S T R A C T Bile acid production in cerebrotendinous xanthomatosis (CTX) is subnormal, yet the activity of cholesterol 7a-hydroxylase, the rate-determining enzyme of bile acid synthesis, is elevated. To explain this discrepancy, bile acid precursors were sought in bile and feces of three CTX subjects. Over 10% of the total sterols excreted in bile and feces consisted of compounds more polar than cholesterol. Chromatographic analysis of the polar fractions in conjunction with gasliquid chromatography (GLC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…As shown in the present work, the microsomal 25-hydroxylase appears to be specific for 5P-cholestane-3a,7a,12a-triol. This finding can be considered as support for the conclusion by Mosbach and Salen (25) that patients with cerebrotendinous xanthomatosis utilize pathways to cholic acid involving 25-hydroxylation, and explains why these patients have an abnormally high cholic acid/ chenodeoxycholic acid ratio in bile (13).…”
Section: )supporting
confidence: 80%
“…As shown in the present work, the microsomal 25-hydroxylase appears to be specific for 5P-cholestane-3a,7a,12a-triol. This finding can be considered as support for the conclusion by Mosbach and Salen (25) that patients with cerebrotendinous xanthomatosis utilize pathways to cholic acid involving 25-hydroxylation, and explains why these patients have an abnormally high cholic acid/ chenodeoxycholic acid ratio in bile (13).…”
Section: )supporting
confidence: 80%
“…Of particular importance in this respect are the findings by Cronholm and Johansson in the rat (2) and by Bjorkhem et al in man (8) that the major product formed during the incubation of 5,8-cholestane-3a,7a,12a-triol with liver microsomes was 5Pt-cholestane-3a,7a,12a,-25-tetrol and not 5,3-cholestane-3a,7a,12a,26-tetrol. Our own studies have shown that patients with cerebrotendinous xanthomatosis (CTX)' accumulate 25-hydroxylated bile alcohols in bile and feces (9), and that 5f-cholestane-3a,7a,12a,25-tetrol is transformed into cholic acid both in CTX patients and in normolipidemic subjects (10), a result previously reported by Yamada in the rat (11). While it was known, therefore, that 5j-cholestane3a,7a,12a-triol can be converted to 5,8-cholestane-3a,7a,-12a,25-tetrol in vitro and that the latter could be metabolized to cholic acid in vivo, the individual steps of this pathway remained to be demonstrated.…”
Section: Introductionmentioning
confidence: 55%
“…Total bile acid synthesis as measured by the sterol balance method was reduced 50% (8). Although the exact enzymatic defect in bile acid synthesis in CTX has not been defined completely, the major biochemical abnormality apparently involves the incomplete oxidation of the cholesterol side chain (4). The accumulation of C27 bile alcohols that are 12a-hydroxylated suggests that cholic acid synthesis is impaired, while the deficiency of chenodeoxycholic acid in the bile points to reduced formation of this primary bile acid.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormalities include a marked deficiency of chenodeoxycholic acid in the bile and the excretion of large quantities of bile alcohols that contained 27 carbons in the bile, urine, and feces (3)(4)(5)(6)(7). Virtually all of these bile alcohols are hydroxylated at C-12 and C-25 and when excreted in urine and bile are conjugated at C-3 with glucuronic acid (6,7).…”
Section: Introductionmentioning
confidence: 99%